Fantoma cardíaco antropomórfico dinâmico controlado por arduino - Bandeira, Caroline Kretezel (2019)
Cardiovascular diseases are the largest cause of death in the world, and imaging studies have great relevance for the diagnosis and prognosis of these diseases. Thus, it is important that radiology professionals know how to perform examinations correctly to obtain images with diagnostic quality. In order to do so, phantoms, which are simulating objects, can be used and also be applied as a tool in teaching/learning processes and equipment quality control, without the need to expose patients to radiation unnecessarily. In this context, the objective of this work is to develop a dynamic anthropomorphic cardiac phantom that can simulate pathologies such as cardiac arrhythmias and, therefore, can be applied in teaching and training of radiology professionals to perform cardiac exams. The phantom was constructed from the application of layers of latex on an anatomical model of the human heart. Two valves and a septum were built in the internal part, which simulate the atrioventricular valves and the cardiac septum. In order to simulate the systemic and pulmonary circulation, cannulas were connected between the cardiac chambers. A two-way infuser was used, which was connected to the right atrium of the phantom, through which the fluids were injected for the experiments. To perform the simulation of heart beats, an Arduino Uno was used to control the movement of five servomotors. Four motors performed the compression of the cardiac chambers and one performed the compression of the cannulas to simulate the semilunar valves. Experiments were conducted in a conventional X-ray equipment, in a fluoroscope and in a 64-channel tomograph. From the analysis of the images it can be verified that the injected contrast reached all cardiac chambers and that the developed code made it possible to simulate arrhythmias and to vary the frequency of heart beats. It was possible to noticed the need for more refinements to be made, but the work presents potential to be used for teaching professionals, demonstrating how positioning and parameters alter the quality of the images, and to perform experiments for the improvement of protocols in clinics and hospitals.